Sprint kayaking performance enhancement by isometric strength training inclusion: a randomized controlled trial - Lum, Danny (2021)
Performing isometric strength training (IST) can enhance various sports performance. This study compared the effects of including IST on sprint kayaking performance as compared to traditional strength training. Twenty sprint kayaking athletes (age 22 +- 4 year, stature 1.71 +- 0.09 m, body mass 72.0 +- 11.4 kg) performed a 200-m kayak ergometer time trial (200mTT), isometric squat (IsoSqT), isometric bench press (IsoPress) and isometric prone bench pull (IsoPull) during the preand post-tests. Athletes were randomly assigned to either traditional strength training (TRAD) or IST group. Both groups performed a similar strength training program twice a week for six weeks. However, half the volume for squat, bench press and prone bench pull were replaced by IsoSqT, IsoPress and IsoPull, respectively, for the IST group. IsoSqT was performed at 90º knee angle, while IsoPress and IsoPull were performed at 90º and 120º elbow angles, respectively.